Segmental Testicular Infarction Associated to Torsion: First Case Report in Childhood - Mohammed Elifranji (13160309) (2020)
Testicular torsion in children is not uncommon emergency problem which occur due to twist in the spermatic cord leading to ischemia or infarction to testicle. Hemorrhagic infarction can occur following testicular torsion is globally; however, in extremely rare situation, such infarction can be segmental. Segmental testicular infarction (STI) was reported in an infant due to epididymitis and a newborn with STI in 1 testicle with complete infarction in the contralateral testicle due to birth trauma. To best of our knowledge, our case of STI in a child associated with testicular torsion is the first described in the literature. Other Information Published in: Urology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.urology.2020.07.056